2013
DOI: 10.1177/0960327112472353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1.8 GHz radiofrequency radiation on protein expression in human lens epithelial cells

Abstract: The shotgun proteomics technique can be applied to screen the proteins with differential expression between hLECs exposed to 1.8 GHz RF and hLECs sham-exposed to 1.8 GHz RF, and three protein biomarkers associated with RF radiation were validated by Western blot assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Nonetheless, this discrepancy is exciting and warrants further investigation. [56,110,111,112] 22 13 (59.1%) 9 (40.9%) 0.119 Human Leukocytes, human blood neutrophils, human white blood cells [55,69,75,85,113,114,115,116,117,118,119] [171,181,182,183,184,185,186,187,188,189,190] 38 30 (78.9%) 8 (21.1%) 1.779e-04…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, this discrepancy is exciting and warrants further investigation. [56,110,111,112] 22 13 (59.1%) 9 (40.9%) 0.119 Human Leukocytes, human blood neutrophils, human white blood cells [55,69,75,85,113,114,115,116,117,118,119] [171,181,182,183,184,185,186,187,188,189,190] 38 30 (78.9%) 8 (21.1%) 1.779e-04…”
Section: Resultsmentioning
confidence: 99%
“…The latter is exemplified by CYP21A2, which is necessary for the mineralocorticoid and glucocorticoid production in the adrenal glands, and whose deficiency leads to most cases of congenital adrenal hyperplasia (Miller and Auchus, 2011). Recently several pathogenic variants of CYP21A2 have been linked to autosomal dominant congenital cataracts (Berry et al, 2022), and earlier CYP21A2 was detected in cultures of human lens epithelial cells (Zhang et al, 2013). Collectively, these findings suggested that CYP21A2 could be important for biosynthesis of aldosterone and cortisol in the lens.…”
Section: Steroidogenic P450smentioning
confidence: 99%
“…Conversely, a different group found that 19,20-EDP and 17,18-EEQ suppressed laser-induced CNV in mice ( Yanai et al, 2014 ) and that animals overexpressing CYP2C8 in endothelial cells and fed the DHA+EPA-enriched diet had markedly attenuated neovascular lesions ( Hasegawa et al, 2017 ). Apparently, the individual effects of 19,20-EDP, 14,15-EET, and 17,18-EEQ on ocular neovascularization need to be investigated to resolve the conflicting data on the CYP2C8 ocular significance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to healthy cells also being affected by SRP72 depletion, a drug inhibition of SRP72 is unlikely to be a useful strategy for radiotherapy treatment, but SRP72 levels can be a biomarker for radiosensitivity. Interestingly, an independent study reported that SRP68 expression decreased significantly, suggesting it as a biomarker, in human lens epithelial cells exposed to radiofrequency radiation ( Zhang et al, 2013 ).…”
Section: Srp and Diseasesmentioning
confidence: 99%